1987
DOI: 10.1212/wnl.37.5.749
|View full text |Cite
|
Sign up to set email alerts
|

Tick‐bite meningoradiculoneuritis

Abstract: We studied 10 adults with meningoradiculitis several weeks after a tick bite (Ixodes). EMG evidence of denervation was associated with normal motor conduction velocities, prolongation of distal latencies, and low sensory amplitudes, suggesting axonal neuropathy. Sural nerve biopsies confirmed the axonal involvement. Infiltrations of lymphocytes and plasma cells, sometimes forming thick pericapillary cuffs with no accompanying necrosis of vessel walls, were numerous. Many capillaries of the endoneurium, perineu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
2

Year Published

1987
1987
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(35 citation statements)
references
References 1 publication
2
29
0
2
Order By: Relevance
“…Under physiological conditions the spinal roots do not enhance within the dural sac [38]. In neuroborreliosis, pathological studies have demonstrated an endoneural perivascular infiltration of lymphocytes and plasma cells in peripheral nerves [5,42]. Epineural vasculitis has been considered the main pathogenetic mechanism of polyneuritis in borreliosis [ 13,19].…”
Section: Discussionmentioning
confidence: 99%
“…Under physiological conditions the spinal roots do not enhance within the dural sac [38]. In neuroborreliosis, pathological studies have demonstrated an endoneural perivascular infiltration of lymphocytes and plasma cells in peripheral nerves [5,42]. Epineural vasculitis has been considered the main pathogenetic mechanism of polyneuritis in borreliosis [ 13,19].…”
Section: Discussionmentioning
confidence: 99%
“…Neither spirochete antigens nor complement are typically demonstrable at the sites of inflammation. [20][21][22] This circumstance has resulted in several hypotheses regarding the pathophysiology of disease.…”
Section: Lyme Pathophysiologymentioning
confidence: 99%
“…49 Histopathology of affected peripheral nerves in experimental monkeys, and in the few human biopsies that are available, demonstrates patchy perineural and perivascular lymphocytic infiltrates. 21,22 Although a few small series provide neurophysiologic evidence of Guillain-Barre-like demyelination, all experimental and virtually all clinical data demonstrate a multifocal inflammatory disorder with loss of axons, a mononeuropathy multiplex ( Table 1). 38,50,51 Clinical presentations include the following:…”
Section: Peripheral Nervous System Involvementmentioning
confidence: 99%
“…The discussion below is based on a review of the nerve biopsy literature in Lyme disease (Meurers et al 1990 ;Vallat et al 1987 ;Meier et al 1989 ;Camponovo and Meier 1986 ;Kristoferitsch et al 1988 ;Halperin et al 1987 ;Tezzon et al 1991 ;Hansen et al 2013 ). Lyme organisms have never been reported in peripheral nerve.…”
Section: Pathologymentioning
confidence: 99%